Таксономія і систематика роду Сolchicum L. (Соlchicaceae A.P. De Candolle) - Gnatiuk, A.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
It is critically analyzed a taxonomic status of genus Colchicum L. Different authors' systematic position of a genus Colchicum L. is presented. The species list of a genus is given.